Etika Komunikasi Levinas dalam Pengarusutamaan Gender di Lingkungan Perusahaan - Lia Rahayu Utami; Novia, Reni (Communicology: Jurnal Ilmu Komunikasi, 2025)
This research aims to examine the implementation of gender mainstreaming at PT Eagle Industry Indonesia through the ethical approach of Emmanuel Levinas, particularly the concept of the Other and the responsibility towards "the face of the Other." Female industrial workers often bear the burden of dual roles that are not only functional but also rich in ethical and existential dimensions. In this context, gender mainstreaming cannot be viewed solely from a structural or administrative perspective, but rather needs to be analyzed from the ethical relations between subjects as theorized by Levinas. This research uses a qualitative approach within the critical paradigm, with a case study method and data collection techniques through in-depth interviews and company policy documentation. The research results show that although the company has adopted policies supporting gender equality, the recognition of women's experiences as unique and irreplaceable subjects is still limited. Levinas's perspective provides a fundamental basis for understanding the importance of relationships characterized by unconditional responsibility towards "the other," so that gender policies do not merely become formalities, but rather manifestations of a more humane relational ethics. This study recommends the need for a shift from a bureaucratic approach to an ethical approach in formulating and implementing gender policies in the industrial workplace, because gender mainstreaming policies should not only be written but also applied equally to all employees.The conclusion of this study is that the implementation of gender mainstreaming policies at PT Eagle Indonesia is still administrative in nature and has not yet addressed cultural aspects. This means that there is still a structural bias in the job promotion system and division of labor that favors masculinity.